2021
DOI: 10.1002/adma.202101903
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Blue Light Emitting Diodes Based On Europium Halide Perovskites

Abstract: Flat panel displays enjoy 100 billion‐dollar markets with significant penetration in daily life, which require efficient, color‐saturated blue, green, and red light‐emitting diodes (LEDs). The recently emerged halide perovskites have demonstrated low‐cost and outstanding performance for potential LED applications. However, the performance of blue perovskite LEDs (PeLEDs) lags far behind red and green cousins, particularly for color coordinates approaching (0.131, 0.046) that fulfill the Rec. 2020 specification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
113
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 46 publications
3
113
1
Order By: Relevance
“…Most recently, stable inorganic lead-free perovskites (e.g., CsEuBr 3 , Cs 3 Cu 2 X 5 , and Cs 3 Sb 2 X 9 ) have been designed for the fabrication of durable blue PeLEDs. [267][268][269][270][271] In particular, bivalent lanthanide ions have similar ionic radius to that of Pb 2+ and possess superior luminescence properties. The emission of lanthanide and actinide compounds can range from deep blue to infrared; thus, a series of novel perovskites remain to be developed for use in stable PeLEDs.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, stable inorganic lead-free perovskites (e.g., CsEuBr 3 , Cs 3 Cu 2 X 5 , and Cs 3 Sb 2 X 9 ) have been designed for the fabrication of durable blue PeLEDs. [267][268][269][270][271] In particular, bivalent lanthanide ions have similar ionic radius to that of Pb 2+ and possess superior luminescence properties. The emission of lanthanide and actinide compounds can range from deep blue to infrared; thus, a series of novel perovskites remain to be developed for use in stable PeLEDs.…”
Section: Discussionmentioning
confidence: 99%
“…1–3 Their exceptional electronic and optical properties also encourage researchers to explore potential applications beyond solar cells. 4–8 In particular, low-dimensional organic–inorganic metal halides have been considered as efficient emitters due to the merits of structural and compositional tunability, extraordinary optical properties and facile synthesis by wet and solid-state methods, 9–17 which are potentially used in display technologies, solid-state lighting, scintillators, remote thermography and anti-counterfeiting labeling. 18–25 Notwithstanding the rapid advance in materials’ diversity and photoluminescence (PL) efficiency, their fundamental photophysical mechanisms are still elusive, which needs to be clarified not only from a basic science point of view, but for the purpose of designing novel materials with exceptional PL properties for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that, as the central wavelength of EL approaches these wavelengths, the peak EQEs and operational lifetimes drop considerably. [25,118,[123][124][125][126][127][128] Figure 1. Schematic of general PeLED device structures, and energy levels of some commonly used HTL, ETL, and emissive perovskite materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that, as the central wavelength of EL approaches these wavelengths, the peak EQEs and operational lifetimes drop considerably. [ 25,118,123–128 ]…”
Section: Introductionmentioning
confidence: 99%